36 Monte Carlo simulation of absorbed dose distribution for electron beam using GATE/GEANT4. (December 2018) - Leste, J.; Younes, T.; Chauvin, M.; Vieillevigne, L.; Bardies, M.; Franceries, X.; Nalis, J.; Simon, L.
Abstract : Introduction: Limits of Treatment Planning Systems (TPS) dose calculation for photon beams have been widely studied. There are fewer studies on electron beam dose calculation. Fast Electron Monte Carlo (eMC, Varian, Palo Alto, CA) is a clinical dose distribution calculation algorithm for electron beam, based on an advanced variance reduction technique, Macro Monte Carlo (MMC)[1] . Results for complex cases (heterogeneity, irregular surface contour) are limited. A GATE/GEANT4 model of a radiotherapy linac (Varian, TrueBeam) is implemented. The purpose of this study is to evaluate these algorithms by comparing them to film measurements in complex cases. Methods: Validation of GATE model is performed on homogenous water phantom. Percentage depth dose curves (PDD) and lateral dose profiles (LDP) are compared with experimental measurement (6 and 9 MeV). Results of dose distribution calculation for eMC and GATE are comparing with Gafchromic EBT3 (Ashland ISP, Wayne, NJ) films, for complex cases including heterogeneities (lung, bone) and irregular surface (step). Normalization are achieved in a homogenous water region for dose profiles at two different depths (at contact and at a distance of the heterogeneity). Global Gamma Index Pass Rate (GIPR) 1D is used to compare the data sets. Results: When comparing GATE and measurements, GIPR 2 % / 2 mm for PDD and LDP in homogenous water phantom is 100% for 6 MeV and 9 MeV. GIPR 3 % / 3 mm (threshold >10% D max ) for complexes cases (lung, bone and step) is >98.5% for GATE (6, 9 MeV) except for only one case at 6 MeV (at contact with lung heterogeneity: 82.9%). But, for eMC in lung case, GIPR are 100% for 9 MeV electrons but only 65.6% and 84.4% at 6 MeV at contact and at 10 mm of the heterogeneity, respectively. In presence of bones, GIPR are 100% (6, 9 MeV) except at 9 MeV, at contact of the heterogeneity (69.7%). For irregular surface cases GIPR of eMC vs. films was superior to 95.2% and 99.2% for 6 and 9 MeV respectively. Conclusions: GATE model for electron beams is validated in homogeneous water phantom. In presence of surface irregularities (step) satisfactory results are obtained for both GATE and eMC. Nevertheless, when comparing to measurements for heterogeneous media, and in particular after lung (6 MeV) and bones (9 MeV) eMC was limited while GATE was satisfactory in all configurations. The study is currently carried on for more energy (12 and 18 MeV) and clinical cases (face). GATE could be proposed as a 3D dose check solution for complex electron beams.